EVALUASI TERHADAP PELAKSANAAN PEMBELAJARAN INOVATIF PADA GURU SMA YANG TERSERTIFIKASI DAN SOLUSINYA DIKOTA SURAKARTA - Dwiastuti, Sri; Witurachmi, Sri; Susilohadi, Gunarso; Yamtinah, Sri (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2010)
ABSTRACTThe aim of this research is to find to what extent senior highschool teachers has applied innovative teaching after passing the certification examination. In addition, this research has the aim to find out the problems that the teachers have in their application of innovative teaching. Based on the problems, this research proposes some recommendations for the solutions for the problems.Specifically, this research wants to find out whether there are any differences in the application of innovative teaching between the teachers who passed the portofolio ceritification exam  and those who passed the exam in  the Teacher Profession Education and Training (PLPG).   This is a qualitative research with observation, depth-interview, questionnaire used as the instruments to get the data of the research. The objects of the research are certifiedb and non-certified senior highschool teachers of  natural science, social science, Indonesian and English of both the private and state schools in SurakartaThe research has obtained the following findings. The certification program has created an impact on both certified and non-certified senior highschool teachers in Surakarta. With their limitations, they tend to implement innovative teaching. There is a  difference between certified teachers and non-certified teachers. The former teach better than the later. There is a slight difference between the cerified teachers who passed the portofolio exam and the certified teachers who passed the PLPG exam. The portofolio teachers teach more innovatively than the PLPG teachers.The research has also found that the teachers are facing some problems that discourage them to implement innovative teaching. First, they are forced to prepare the students for the National Exam. Secondly, they have the wrong perception that teaching innovatively means using computers or laptops and this means being expensive. To solve the problems, there should be a continuous supervision and monitoring and evaluation for the teachers.                        .                                                                                              Keywords: innovative teaching, teacher certification,  professional teachers